Assessment of the facilitation process of establishing a living lab for co-creating locally-led climate action in Caquetá/Colombia - Falk, Thomas; Rodríguez, Luz A.; Vanegas, Martha; Nehring, Ryan; Calle, Johana; Lopez, Maria (International Food Policy Research Institute, 2025)
One of the key ambitions of the CGIAR Climate Action Program is to support structures that enable affected people to take ownership of food system innovation processes and to determine their goals, strategies, and modalities. To this end, the program team adopts and expands the concept of living labs, understood as social spaces - virtual or physical - where stakeholders co-develop new ways of thinking and acting to transform collaboration and practices.